(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
The side effects of 9 insecticides and 5 acaricides on the phytoseiid mite Amblyseius andersoni (Chant) were tested in laboratory. Benzomate + propargite, amitraz, fenvalerate, fenpropathrin, endosulfan + methomyl, acephate + dimethoate and malathion, had a negative influence both on young stages and on young adults (1 day old); in both cases mortality was 100%. Abamectin and methyl-parathion were considered not very harmful. Other tested pesticides (hexythiazox, chlorpyrifos, benzomate, clofentezine, buprofezin) were harmless as the mortality of young stages ranged from 10% to 36% and the mortality of adults was null. According to these results the latter pesticides could be used in an IPM programme.